Análise da finalidade econômica da lei de recuperação judicial e falência de empresas no Brasil com base na teoria dos custos de transação - Buchabqui, Tárik Capisani Buchabqui (2021)
The economic purpose of the Reorganization and Bankruptcy Law in Brazil is to preserve the company, it’s social function and stimulate the economy. This article critically analyzes whether the legal mechanisms provided by this legislation are following the economic orientation of reducing the transaction costs involved in the judicial process. The analysis showed that the transaction costs of the judicial process are high and these enefficiencies may be contributing to the low practical result of this legislation, raising doubts as to whether its economic purpose is being achieved.